mechanism of protection of proposed Geopark West of Khorasan Razavi by brilha method - Mohammad Ali Zanganeh Asadi; Abolghasem Amirahmadi; ali akbar shayan yeganeh (نشریه جغرافیا و برنامه‌ریزی, 2018)
Geotourism, encourages tourism into geosite and conservation of geodiversity and an understanding of earth sciences. One way to effectively protection and conservation geodiversity is that valuable parts such as geoheritage (geological and geomorphological heritage) are  protect and conserved. Most  of human-scale geological materials  are non-renewable. Geoparks are special territories with a development plan that their aim is protection of geological heritage (and other natural resources) while preserving the cultural identity of local communities. Iran has a wide range of geological and geomorphological phenomena that geotourism recently formed and located during the early stages of development. The paper attempts to analyze and evaluate based on geomorphosites and geosites in West of Khorasan Razavi, one of the common methods (method Brilha), could be offered the optimal mechanism for the protection and benefit of geodiversity (geoconservation).